2020
DOI: 10.3390/rs12244074
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Early Warning System for Health Issues Related to Particulate Matter Exposure in Brazil: The Feasibility of Using Global PM2.5 Concentration Forecast Products

Abstract: PM2.5 severely affects human health. Remotely sensed (RS) data can be used to estimate PM2.5 concentrations and population exposure, and therefore to explain acute respiratory disorders. However, available global PM2.5 concentration forecast products derived from models assimilating RS data have not yet been exploited to generate early alerts for respiratory problems in Brazil. We investigated the feasibility of building such an early warning system. For this, PM2.5 concentrations on a 4-day horizon forecast w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Piasecki and Kostyrko [93] developed a method based on a decision matrix that includes six attributes: actual indoor air CO 2 concentration, TVOCs, and formaldehyde concentration, and their anthropogenic and construction product emissions to the indoor environment with a combined weighting scheme for an IAQ index equation. Kim et al [94] suggested an IAQ index which reflects PM 2.5 and CO 2 , divided into five grades from "good" to "hazardous" with a scale of 1 to 100 points, as follows: "good" (0-20); "moderate" (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40); "unhealthy for a sensitive group" (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60), "bad" (61-80), and "hazardous" (81)(82)(83)…”
Section: Methodology and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Piasecki and Kostyrko [93] developed a method based on a decision matrix that includes six attributes: actual indoor air CO 2 concentration, TVOCs, and formaldehyde concentration, and their anthropogenic and construction product emissions to the indoor environment with a combined weighting scheme for an IAQ index equation. Kim et al [94] suggested an IAQ index which reflects PM 2.5 and CO 2 , divided into five grades from "good" to "hazardous" with a scale of 1 to 100 points, as follows: "good" (0-20); "moderate" (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40); "unhealthy for a sensitive group" (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60), "bad" (61-80), and "hazardous" (81)(82)(83)…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…These particles can vary in size, shape, and composition. PM that are 10 µm in diameter or smaller (for instance, PM 2.5 ) are inhalable and can affect the lungs, causing acute respiratory disorders [56]. PM 2.5 may also play a role in mental health conditions, such as major depressive disorder [34].…”
Section: Pm 25mentioning
confidence: 99%
“…Recently, some products with high temporal and spatial resolutions from geostationary-orbit satellites have been available. Several studies assessed the relationship of PM 2.5 and mortality, using satellite-derived estimations [ 22 – 28 ], mainly in the USA, Europe and Southeast Asia. Limited studies are available in South America [ 29 – 33 ].…”
Section: Introductionmentioning
confidence: 99%